Musa balbisiana and Musa paradisiaca Starches Increase SCFA and Caspase-3 as well as Decrease β-glucuronidase and MDA of Mouse Model for Colon Cancer - Diana Nur Afifah; Fauzia Purnamasari; Luthfiatul Khusna; Noviasti Rahma Utami; Aida Fitri Nazillah; Syafira Noor Pratiwi; Fillah Fithra Dieny; Aryu Candra; Ayu Rahadiyanti; Rachma Purwanti; Enny Probosari; Martha Ardiaria; Nyoman Suci Widiastiti; Ferry Sandra (The Indonesian Biomedical Journal, 2021)
BACKGROUND: Administration of resistant starch (RS) influences the diversity and the composition of microbiota as well as inhibits the growth of cancer cell. Banana as a potential source of RS has been reported. Although Musa paradisiaca has been reported to induce apoptosis in colon cancer cells, Musa balbisiana, which has low glycemic index and suitable for particular patients, has not been investigated yet.METHODS: Starches of M. balbisiana and M. paradisiaca were prepared and mixed with other components to make 3 types of mouse pellets. Mouse model for colon cancer was prepared and fed with different types of mouse pellets. Blood was collected and processed for measuring β-glucuronidase and malondialdehyde (MDA) with Enzyme-linked Immunosorbent Assay (ELISA) method. Resected ceca were incised to collect the inner part for short-chain fatty acid (SCFA) measurement with gas chromatography analysis. Resected colas were fixed and processed for immunohistochemistry to detect Caspase-3.RESULTS: Colon-cancer-mice fed with the M. balbisiana and M. paradisiaca starches-contained pellets had significant higher concentrations of total SCFA (p=0.003), acetic acid (p=0.000), propionic acid (p=0.000) and butyric acid (p=0.000); lower concentration of β-glucuronidase (p<0.001); higher Caspase-3 score (p=0.040); and lower MDA concentration (p<0.001) than colon-cancer-mice fed with standard pellet (control).CONCLUSION: M. balbisiana and M. paradisiaca starches could be suggested as potential anti-colon cancer RS. Further research should be carried out to disclose the starches mechanisms in colon cancer cell.KEYWORDS: Musa balbisiana, Musa paradisiaca, colon cancer, resistant starch, Caspase-3, SCFA, β-glucuronidase, malondialdehyde